Paradigm Shift of Language Revitalization in Indonesia - Budiono, Satwiko; Yanita, Selly Rizki; Syarfina, Tengku (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
Language revitalization as a linguistic social movement that aims to preserve and promote local languages, is experiencing a paradigm shift in Indonesia. These shifts can be seen from the aspect of language status objects. That is meant here is that the object of language status in language revitalization is not only languages with minority and endangered status. All local languages in Indonesia can be revitalized. Based on these conditions, this study explores the shift in the language revitalization paradigm in Indonesia. This aims to explain the structure of paradigm shift and provide an explanation for understanding language revitalization in its historical development in Indonesia. The study method uses qualitative methods with data collection techniques from the results of literature studies. Data analysis refers to Thomas Samuel Kuhn’s structure of the scientific revolution in terms of paradigm shift. As a result, the shift in the language revitalization paradigm in terms of the language status object is based on the heterogeneity of languages in Indonesia. Meanwhile, all languages in Indonesia must and have the right to be preserved in accordance with statutory regulations. This condition makes the government regulate language revitalization regulations that apply to all languages so that all languages in Indonesia receive the same treatment in the context of language preservation efforts.